Physical activity and screen time behavior, and non-alcoholic beverage consumption during the COVID-19 pandemic in the longitudinal study of adult health (ELSA-Brasil) - Mercadante Urquía, Yazareni José; Martins, Haysla Xavier; Silva Pereira, Taísa Sabrina; Batista de Azevedo, Letícia; Lopes Júnior, Luís Carlos; Molina, Maria Del Carmen Bisi (Frontiers in Nutrition, 2025)
BackgroundThe COVID-19 pandemic affected various dietary and lifestyle behaviors. Understanding the relationship between physical activity, screen time, and beverage consumption is critical to identify at-risk populations, particularly individuals with chronic non-communicable diseases (NCDs), for targeted intervention strategies.ObjectiveThis study aimed to evaluate the relationship between physical activity, screen time behavior patterns, and non-alcoholic beverage consumption among participants in ELSA-Brasil during the COVID supplementary study.MethodsThe study was conducted in five of the six ELSA-Brasil research centers, from July 2020 to March 2021. Sociodemographic variables, physical activity, screen time, non-alcoholic beverage consumption, and lifestyle factors were analyzed using bivariate analyses and binary logistic regression models.ResultsThe total sample consisted of 4,442 participants with a mean age of 62.0 ± 8.6 years. Significant gender differences were found in sociodemographic and lifestyle variables, influencing beverage consumption patterns. Participants with excessive screen time and physical inactivity were more likely to consume sugar-sweetened beverages. Specifically, men exhibited a significant association with an odds ratio of 2.44 (95%CI: 1.54–3.84), while women had an odds ratio of 1.72 (95% CI: 1.02–2.91). Men with appropriate screen time but physically inactive behavior had nearly double the likelihood of consuming sugar-sweetened artificial beverages. Additionally, men with excessive screen time and physical inactivity had higher consumption of industrialized juices (OR: 1.93; 95% CI: 1.22–3.06), while women were more likely to consume soft drinks (OR: 2.28; 95%CI 1.10–4.72).ConclusionThese findings underscore the importance of addressing both screen time and physical activity in public health initiatives, through gender-specific approaches that account for socioeconomic disparities when prioritizing interventions.